KARAKTERISTIK LAGU-LAGU KEBANGSAAN ARAB: ANALISIS FONOLOGI - Tazkiyyatul Amanah; Puspita Herwening (Lughawiyah: Journal of Arabic Education and Linguistics, 2021)
This study aims to determine the phonetic characteristics of the Arabic national anthems. The object of this research is the national anthems of three countries, namely Saudi Arabia, Egypt, and Morocco. This research used a linguistic-phonetic approach. Data analysis used quantitative descriptive analysis. The results described that there were differences in vowel and consonant characteristics between the national anthems of Saudi Arabia, Egypt, and Morocco. Based on the number, the comparison in the national anthems of Saudi Arabia, Egypt, and Morocco was 84:156:142 for vowels, 15:44:19 for semi-vowels, and 82:161:110 for consonants. The Egyptian national anthem used long vowels (31.4%) more dominantly than the national anthems of Saudi Arabia and Morocco, while the Saudi Arabian national anthem used more thick (6%) and semi-thick (6%) vowels compared to Egyptian and Moroccan national anthems. For the consonant level, the three national anthems were dominated by alveodental consonants, the letters that come from the tip of the tongue, namely 39% for the Saudi Arabian, 34.2% for the Egyptian, and 36.4% for the Moroccan national anthems.Â